Risk pathways and prevalence in slaughtered pig blood of Streptococcus suis in Vietnam - Sinh Dang Xuan; Bryant, J.E.; Unger, Fred; Bao Ngo-Thanh; Bich Vu Thi Ngoc; Phuc Pham Duc; Grace, Delia; Hung Nguyen-Viet (Hanoi School of Public Health, 2015)
Streptococcus suis is a leading cause of bacterial meningitis in Vietnamese adults, and the major risk factors have been identified as consumption of raw pig blood (Tiet canh), and occupational exposure to pigs. Previous studies of S. suis prevalence in pigs sampled from southern Vietnam have indicated very high levels of commensal infection in tonsil specimens, however there is relatively little data on prevalence rates of systemic infections in pigs (as indicated by detection from fresh blood), and prevalence rates from northern and central Vietnam have yet to be described. To address these data gaps, we sampled blood from 147 slaughtered pigs in two provinces Hung Yen (North) and Nghe An (Center) and analyzed for S. suis using PCR (16S- S. suis and S. suis serotype 2). In addition, we surveyed 406 heads of household and 51 slaughterhouse workers in these areas to understand behaviors and attitudes toward consumption of raw pig blood. A total of 33.3% of 147 pig blood samples tested positive with S. suis, but only 1.4% (2/147) were positive to S. suis serotype 2, the serotype most frequently associated with severe human infections. Fifteen of 406 people interviewed (3.4%) reported eating ‘Tiet canh’, whereas this rate was significantly higher at 43.1% (21 of 51) for slaughterhouse workers. These findings will be discussed in the context of the growing body of literature on S. suis epidemiology, culinary practices involving raw or undercooked pig products, and risk mitigation strategies to minimize disease transmission.